Leishmania spp: Delta-aminolevulinate-inducible neogenesis of porphyria by genetic complementation of incomplete heme biosynthesis pathway - Dutta, Sujoy (2007)
To further develop the Leishmania model for porphyria based on their deficiencies in heme biosynthesis, three Old World species were doubly transfected as before for Leishmania amazonensis with cDNAs, encoding the 2(nd) and 3(rd) enzymes in the pathway. Expression of the transgenes was verified immunologically at the protein level and functionally by uroporphyrin neogenesis that occurs only after exposure of the double-transfectants to delta-aminolevulinate. All species examined were equally deficient in heme biosynthesis, as indicated by the accumulation of uroporphyrin as the sole porphyrin and the production of coproporphyrin upon further transfection of one representative species with the downstream gene. The results obtained thus demonstrate that at least the first five enzymes for heme biosynthesis are absent in all species examined, rendering their transfectants inducible with aminolevulinate to accumulate porphyrins and thus useful as cellular models for human porphyrias.